2020
DOI: 10.1097/aln.0000000000003077
|View full text |Cite
|
Sign up to set email alerts
|

Oral Dimethyl Fumarate Reduces Peripheral Neuropathic Pain in Rodents via NFE2L2 Antioxidant Signaling

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background Available treatments for neuropathic pain have modest efficacy and significant adverse effects, including abuse potential. Because oxidative stress is a key mechanistic node for neuropathic pain, the authors focused on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 50 publications
4
56
0
Order By: Relevance
“…142 The antinociceptive effects produced by the administration of different Nrf2 activators, such as sulforaphane, oltipraz, plumbagin, and dimethyl fumarate, have been evaluated. Several studies have shown that the pharmacological activation of Nrf2 reduces acute and chronic inflammatory pain 12,19,143 and neuropathic pain associated with diabetes 20,59 generated by nerve injury 75,93,144,145 or induced by chemotherapeutic drugs in rodents. 146 In contrast, the loss or disruption of Nrf2 signaling causes increased susceptibility to oxidative stress and inflammatory injuries.…”
Section: Activation Of Ho-1 and Carbon Monoxide Modulates The Antinmentioning
confidence: 99%
See 3 more Smart Citations
“…142 The antinociceptive effects produced by the administration of different Nrf2 activators, such as sulforaphane, oltipraz, plumbagin, and dimethyl fumarate, have been evaluated. Several studies have shown that the pharmacological activation of Nrf2 reduces acute and chronic inflammatory pain 12,19,143 and neuropathic pain associated with diabetes 20,59 generated by nerve injury 75,93,144,145 or induced by chemotherapeutic drugs in rodents. 146 In contrast, the loss or disruption of Nrf2 signaling causes increased susceptibility to oxidative stress and inflammatory injuries.…”
Section: Activation Of Ho-1 and Carbon Monoxide Modulates The Antinmentioning
confidence: 99%
“…140 The principal mechanisms involved in the antinociceptive effects of the Nrf2 transcription factor during acute and chronic pain are the enhancement and/or normalization of Nrf2, HO-1, NQO1, glutathione transferase or superoxide dismutase expression and the inhibition of microglial activation, NOS2 overexpression and MAPK phosphorylation in the spinal cord, dorsal root ganglia and/or paw tissues. 12,19,143,144 Other studies have revealed that the administration of Nrf2 inducers also reduces inflammatory responses by decreasing the synthesis of cyclooxygenase-2, TNF-α, IL-1β, and/or IL-6. 144,147,148 The prevailing oxidative stress conditions provoked by nerve injury in the peripheral and central nervous system, which are represented by reduced expression of Nrf2 and HO-1 in the spinal cords, amygdalas, prefrontal cortices, and hippocampi of animals with sciatic nerve injury-induced neuropathic pain, 54 are normalized by treatment with sulforaphane or oltipraz.…”
Section: Activation Of Ho-1 and Carbon Monoxide Modulates The Antinmentioning
confidence: 99%
See 2 more Smart Citations
“…in addition, dMF has been reported to exert protective effects against i/r injury in the brain (18). dMF is recognized as a potent antioxidant (19) that exerts profound effects on the modulation of apoptosis (20). it has also been shown to activate the nuclear factor erythroid 2-related factor 2 (nrf2) signaling pathway.…”
Section: Introductionmentioning
confidence: 99%